Inclusive Education System in Indonesia: Challenges, Benefits and Implications for Basic Learning - Muhamad Rhenaldi; Lintang Darma Putria; Lucky Haikal; Melati Pardede; Meysah Nabila (R-Disa: Riset Inovasi Pendidikan Guru Sekolah Dasar, 2026)
Inclusive education in Indonesia aims to ensure equal learning opportunities for all students, including those with special needs. This insight summarizes the challenges, benefits, and learning implications of inclusive education based on recent literature from 2023–2025. Major challenges include limited teacher competency in differentiated instruction, insufficient Special Assistant Teachers (GPK), weak curriculum adaptation, and inadequate accessibility facilities. Cultural stigma toward students with special needs also hinders inclusivity. Despite these issues, inclusive education offers significant benefits such as higher empathy, social competence, and improved adaptive teaching practices. Successful implementation requires comprehensive support through teacher training, strengthened school management, accessibility improvement, and active collaboration among parents, teachers, and policymakers.